2020
DOI: 10.1039/d0nr05601d
|View full text |Cite
|
Sign up to set email alerts
|

Spectral shift, electronic coupling and exciton delocalization in nanocrystal dimers: insights from all-atom electronic structure computations

Abstract: Delocalization of excitons promoted by electronic coupling between clusters or quantum dots (QD) changes the dynamical processes in nanostructured aggregates enhancing energy transport. A spectroscopic shift of the absorption spectrum...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 93 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…20,29 Moreover, strongly coupled dimers of colloidal QDs have been designed and the possibility of excitonic delocalization over the two units has been discussed, based on both theoretical and experimental evidences. 50,75–79 How weak and strong-coupling are associated with specific spectral features in A-2DES maps is a critical issue which is left for future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,29 Moreover, strongly coupled dimers of colloidal QDs have been designed and the possibility of excitonic delocalization over the two units has been discussed, based on both theoretical and experimental evidences. 50,75–79 How weak and strong-coupling are associated with specific spectral features in A-2DES maps is a critical issue which is left for future work.…”
Section: Discussionmentioning
confidence: 99%
“…This journal is © the Owner Societies 2022 been discussed, based on both theoretical and experimental evidences. 50,[75][76][77][78][79] How weak and strong-coupling are associated with specific spectral features in A-2DES maps is a critical issue which is left for future work.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…This requires the controlled placement of a second quantum system in close proximity. 13 The chemical bond serves as a basis of molecule formation with electronically coupled atomic states, enabling tunneling of the electrons and delocalization throughout the new hybridized molecular state. 2 Similarly, close proximity of two quantum dots with a minimal barrier engenders hybridized electron wave function delocalized throughout the double quantum dot structure, forming a quantum molecule.…”
Section: From Artificial Atom To Artificial Moleculesmentioning
confidence: 99%
“…The observations of the artificial atom character of CQDs inspired the formation of quantum dot molecules where the creation of hybridized excitons can impose novel synergistic functionalities, relevant to numerous applications including in quantum technologies. This requires the controlled placement of a second quantum system in close proximity . The chemical bond serves as a basis of molecule formation with electronically coupled atomic states, enabling tunneling of the electrons and delocalization throughout the new hybridized molecular state .…”
Section: From Artificial Atom To Artificial Moleculesmentioning
confidence: 99%
“…They found that the dithiocarbamate molecule generates new electronic states close to the band edges of the CdSe QDs, which corroborated the earlier observation. Many other computational studies have also contributed to rationalize the exciton delocalization at the interface of QD-molecule composites. …”
Section: Introductionmentioning
confidence: 99%